You Will Not Remember This: How Memory Efficacy Influences Virtuous Behavior - Touré-Tillery, Maferima; Kouchaki, Maryam (Journal of Consumer Research, 2021)
AbstractThe present article explores the effect of memory efficacy on consumer behavior—particularly on consumer’s likelihood to behave “virtuously,” that is, in line with standards, such as ideals, values, morals, and social expectations. Memory efficacy refers to people’s general belief that they will be able to remember in the future the things they are experiencing or doing in the present. We hypothesize and find across five studies that when consumers have low-memory efficacy (vs. control), they are less likely to behave virtuously because their actions seem less consequential for their self-concept (i.e., less self-diagnostic). Using two different experimental manipulations of memory efficacy, we examine its effect on virtuous behavior in the context of prosocial choices—that is, charitable giving (study 1A) and volunteering (studies 1B and 2). We then explore our proposed underlying mechanism (perceptions of self-diagnosticity) using causal-chain mediation (studies 3A and 3B) and moderation approaches (studies 4 and 5) in the context of food choices. We conclude with a discussion of the practical and theoretical implications of our findings.